FEATURES OF THE FORMATION OF THE ABILITY TO WORK WITH THE BALL BASED ON VISUALMOTOR AND REACTIVE COORDINATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study examined the initial indicators of hand-eye coordination and ball-handling skills among 11–13-year-old girls studying in grades 5–7. The analysis revealed a consistent development of reactive and visuomotor coordination with increasing age. Based on the Student’s t-test, statistical significance (P